Analysis of Driving Factors for the Implementation of Clean Technology to Optimize Green Manufacturing in the Wiradesa Batik Small and Medium Enterprises (SMEs) - Muhammad Slamet Rahajo; Achana Kumyat (Integrated Science Education Journal, 2025)
Purpose of the study: This research aims to improve green manufacturing in the batik SME environment. It must also improve clean technology. Methodology: Give name, brand, type of tools, methods, software, review, and survey that has been used to do this study. No discussion or explanation. Main Findings: The results of the study show that the highest weight is the need for a supply chain (F6) with a weight of 0.443, then the second most important factor is the good name factor of batik SMEs (F2) which is ranked second with a weight of 0.241. Next, the third most important factor is the internal motivation factor (F9) which is ranked third with a weight of 0.088. Followed by other factors until the least important factor is the competitor factor (F11) which is ranked seventh with a weight of 0.036. Novelty/Originality of this study: what is new in this study that may benefit readers and how it is advancing the existing knowledge or creating new knowledge in this subject.